Incorporation of a Non-Conventional Liana (Tetracapidium conophorum) Seed Oil Cake in Diets of Congolese Indigenous Batéké Chicks Raised Without Outdoor Access - Adzona, P. P.; Mopoundza, P.; Ngouama Dandou, A.; Bati, J. B.; Ntsoumou, M. V.; Saya Ngouonomba, H. J.; Bitsili, B. T.; Akouango, P.; Banga-Mboko, H. (European Scientific Journal, ESJ, 2024)
The indigenous Batéké hen (Gallus gallus) has low productivity due to various constraints such as feeding sources. The aim of this study was to improve the productivity of the local hen using a new local protein source: Tetracarpidium conophorum meal. A sample of ninety-six chicks 21-day old from the local population were randomized into 3 groups of 32 birds each (TC0, TC4 and TC6), with one replicate. In each group. Tetracarpidium conophorum oil cake was incorporated into groupsTC4 (4% Tcconophorum oil cake and 11% soya oil cake), TC6 (6% T.conophorum oil cake and 9% soya oil cake) whereas TC0 served as a control group (0% T.conophorum meal and 15% soya oilcake). The experiment started at 3 weeks and lasted at 20 weeks of age. Chickens were fed ad libithum and had free access to drinkers. The results indicated that mortality rate decreased (3.12 % versus 9.3), Also, the treatment improved significantly (p ˂ 0.05) feed intake (56.8 vs 60.1g per day), feed conversion (6.5 vs 5.7), and carcass yield (65.8 % vs 71.3 %). The final body weight at 20 weeks of age has been improved groups (1.200g versus 1300g) .. This study indicated that T.conophorum oil cake may be useful in diets at 4% thus reducing soya oil cake from 15% to 11% of incorporation) in a small scale poultry farming in Congo.